Overview on Creativity and Entrepreneurship in Creative Industries - Santos, Bárbara; Bernardes, Óscar; Amorim, Vanessa; Rua, Orlando Lima (E- Revista de Estudos Interculturais, 2021)
From the music we listen to, to the door we open at work and the chair we sit on right now, creativity is all around us. It has a great contribution in our everyday lives, as nowadays more and more people strive to develop both their imagination and inventiveness. An individual who has nurtured his creativity has an advantage over a person who did not. He or she might bring up an unusual solution, yet effective for a difficult problem, create something unseen or unheard before or even design a new and innovative product - but creativity does not imply an artistic or world-changing creation. Everyday tasks require creativity, therefore almost every individual has developed his inner creativeness to a certain level. “Creative entrepreneurship” is a term which refers to business activity within a creative sector and refers to investment in the entrepreneur’s or others’ talent. The aim of this paper is to offer an overview on creativity and clarify what exactly means to be creative, and to contrast the differences between a regular entrepreneur and one who performs in a creative industry.